A educação em saúde no ensino de ciências e biologia em tempos de pandemia da COVID-19 - Chaves, Leilane Alves (2023)
The thesis was defended in the Postgraduate Program in Education at the Federal University of Uberlândia, in the Education in Science and Mathematics Research Line, and linked to the Body, Gender, Sexuality, and Education research group. Long before the start of the COVID-19 pandemic (March 2020), the approach to Health Education (HE) at school was centered on the biomedical model and diseases. The main lessons of ES presented transmission mechanisms, and the idea of health as an individual phenomenon independent of economic, social, and political conditions. This idea is based on a “universalist” perspective that disregards the specificities and differences in approach regarding, for example, socially excluded groups. In the context of COVID-19, and, considering the emergencies of higher education concerning social, cultural, and economic diversities and the need to produce responses to the developments of the pandemic in school education, the following research question was elaborated: which health education Was it made possible in emergency remote Science and Biology classes in the context? The general objective of this study was to analyze the HE approaches in proposals for emergency remote Science and Biology classes, made available by the State Department of Education of Minas Gerais and the Municipal Department of Education of the city of Uberlândia – MG. The specific objectives were to discuss how the topic was inserted and worked on in emergency remote classes; investigate the type of dialogue established, via ES, with students; highlight the possible contributions of classes to higher education; and reflect on HE, education, and the Teaching of Science and Biology in remote classes. The internet was constituted as the research field and we particularly took the electronic pages of the Departments of Education – state of Minas Gerais and city of Uberlândia, in a theoretical-methodological perspective situated in tools of virtual ethnography referenced by Sueli Fragoso and Luis Paulo Mercado. Theoretically, the notions of education and health, in research, were supported by critical and post-critical matrices, elaborated by the field of Public Health, Education, Science Education, and texts by French philosophers Michel Foucault and Georges Canguilhem. We argue that the emergency remote Science and Biology classes analyzed make up small HE networks. Teachers opened important paths for the reframing of higher education as a collective value by providing students with the recreation of thoughts, resistances, and other ways of seeing the world in the face of the pandemic. The analysis of the material demonstrated that it is possible to recognize the production of possibilities for overcoming conservative notions and rules of conduct. Thus, potentially, school education is seen as a plural space for the construction of higher education for all. The school and higher education constituted a locus for confronting the pandemic.